2011
DOI: 10.1111/j.1600-0536.2011.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy and human biomonitoring - an overview with a focus on metals

Abstract: Humans are widely exposed to chemicals. Today, there is an increased acknowledgement of the importance of measuring human and environmental exposures to man-made or refined chemicals. Different approaches have been applied over time, but during the past 25 years, there has been a general trend towards the use of human biomonitoring. A few studies have used human biomonitoring methodology to track contact allergens together with information on patch test reactivity. Hypothetically, the internal load of reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Cobalt is a known sensitizer (1,2), and can induce allergic contact dermatitis (3,4). Exposure to cobalt on the skin can be easily determined with a skin wash technique (5); however, more knowledge is needed for biological monitoring of contact allergens (6).…”
mentioning
confidence: 99%
“…Cobalt is a known sensitizer (1,2), and can induce allergic contact dermatitis (3,4). Exposure to cobalt on the skin can be easily determined with a skin wash technique (5); however, more knowledge is needed for biological monitoring of contact allergens (6).…”
mentioning
confidence: 99%
“…It has been reported that cobalt and nickel powders penetrate damaged skin more easily compared to intact skin. Little is known about how aging affects skin penetration, apart from the incomplete barrier function observed in infants and young children (Thyssen et al, 2011).…”
Section: Effects On Skinmentioning
confidence: 99%
“…This retrospective information allows for the assessment of nutritional status, environmental and occupational exposure to metals, and body load. [16][17][18][19] Unfortunately, despite the many positive attributes of alternative materials, there are some difficulties associated primarily with the interpretation of the results. The biggest limitation is a properly defined range of reference values of concentration, especially in relation to hair.…”
Section: Introductionmentioning
confidence: 99%